Rebels with a Cause: Formation, Contestation, and Expansion of the De Novo Category “Modern Architecture,” 1870–1975 - Jones, Candace; Maoret, Massimo; Massa, Felipe G.; Svejenova, Silviya (Organization Science, 2012)
Most category studies have focused on established categories with discrete boundaries. These studies not only beg the question of how a de novo category arises, but also upon what institutional material actors draw to create a de novo category. We examine the formation and theorization of the de novo category “modern architecture” between 1870 and 1975. Our study shows that the process of new category formation was driven by groups of architects with distinct clientele associated with institutional logics of commerce, state, religion, and family. These architects enacted different artifact codes for a building based on institutional logics associated with their specific mix of clients. “Modern architects” fought over what logics and artifact codes should guide “modern architecture.” Modern functional architects espoused a logic of commerce enacted through a restricted artifact code of new materials in a building, whereas modern organic architects advocated transforming the profession's logic enacted through a flexible artifact code of mixing new and traditional materials in buildings. The conflict became a source of creative tension for modern architects that followed, who integrated aspects of both logics and materials in buildings, expanding the category boundary. Plural logics and category expansion resulted in multiple conflicting exemplars within “modern architecture” and enabled its adaptation to changing social forces and architectural interpretations for over 70 years.